Delineation process of the extended continental shelf: an interpretation of article 76, paragraph 6, of UNCLOS - Lertora Pinto, Francisco (Revista Chilena de Derecho, 2021)
The 1982 United Nations Convention on the Law of the Sea established specific rules for the delineation of the outer limit of the continental shelf in Article 76. This Article contains two formulae and two constraints. Regarding these constraints, the coastal State can apply, whichever is more favorable to its claim, unless the exception established under Article 76 (6), first sentence, applies. This exception establishes that, on submarine ridges, the State can only apply the 350 nautical miles distance constraint. However, Article 76 (6), second sentence, introduces a counter-exception and preserves the State’s right to apply either constraint when the seafloor high is a submarine elevation that is a natural component of the continental margin.